العلاقة الزوجية في الأسرة (دراسة في جماعة التبليغ والدعوة بمدينة بالو) (State Institute for Islamic Studies Palu, 2019)
This paper discusses the pattern of the husband-wife relationship and the concept of the marriage relationship in the family of Tablighi Jamaat in Palu city. The purpose of this study to reveal the pattern of husband-wife relations and the concept of the marriage relationship in the family of Tablighi Jamaat in Palu city. This research uses a qualitative approach. The data source was gathered through observation, interviews, and written sources. The research findings were that the pattern of husband-wife relation in the family of Tablighi jamaat when viewed from the aspect of the division of domestic labor, livelihood fulfillment and financial management, and decision making are based on cooperation and discussion. The concept of a marriage relationship that the husband is the head of the family. His responsibilities are to guide the family, provides for them financially, and invites people to Allah (da’wah). While the wife is the leader of the household. She is primarily responsible for the upbringing of children, to serve the husband, and stands by him in da’wah. The social rule in Tablighijamaat’s family is the religious teachings in accordance with jamaat principles. The research implication was that Tablighi Jamaat should provide sufficient time for family.